Gothic forms of feminine fictions - Becker, Susanne (Manchester University Press, 2017)
Gothic forms of feminine fictions is a study of the powers of the Gothic in late twentieth-century fiction and film. Susanne Becker argues that the Gothic, two hundred years after it emerged, exhibits renewed vitality in our media age with its obsession for stimulation and excitement. Today's globalised entertainment culture, relying on soaps, reality TV shows, celebrity and excess, is reflected in the emotional trajectory of the Gothic's violence, eroticism and sentimental excess. Gothic forms of feminine fictions discusses a wide range of anglophone Gothic romances, from the classics through pulp fictions to a postmodern Gothica. This timely and original study is a major contribution to gender and genre theory as well as cultural criticism of the contemporary. It will appeal to scholars in a wide range of fields and become essential for students of the Gothic, contemporary fiction - particularly Alice Munro and Margaret Atwood - and popular culture.
Originally published: 1999.
Available through ManchesterHive.
Keywords: Gothic literature -- Women authors.; Gothic revival (Literature) -- Women authors.; Canadian fiction -- Women authors -- History and criticism.; Gothic revival (Literature) -- Canada.; Horror tales, Canadian -- History and criticism.; Horror films.; Motion pictures and women.; Littérature frénétique -- Canada.; Récits d'horreur canadiens -- Histoire et critique.; Films d'horreur.; Cinéma et femmes.; Feminism & Feminist Theory.; SOCIAL SCIENCE / Feminism & Feminist Theory.; Canadian fiction -- Women authors.; Gothic revival (Literature); Horror tales, Canadian.; Canada.; Criticism, interpretation, etc.